Performance of Manufacturing Firms in Africa : An Empirical Analysis - Dinh, Hinh T. (Washington, DC: World Bank, 2012)
This book sheds light on the characteristics of formal and informal manufacturing firms in Africa by comparing these firms with firms in other regions. Drawing on two data sources, the authors find that there is a very low share of manufacturing in GDP in Africa and in African exports. Most African manufacturing firms are informal. These firms are also smaller than firms in other regions and few export. Labor productivity is low in Africa relative to other regions, but this may be because of the more challenging environment - with the lack of physical infrastructure, the heavy burden of business regulation, and other issues. However, after accounting for these differences, the authors find that firms in Sub-Saharan Africa appear more, not less, productive than firms elsewhere. This analysis suggests that improving the business environment might allow firms to enhance their performance. However, given the pervasive distortions in the business environment and the limited resources at the disposal of most African countries, Africa cannot and should not wait until the business environment becomes healthier before growing a more viable manufacturing sector. The book shows that binding constraints vary by country, by sector, and by firm size. Therefore, countries should identify the constraints in the most promising sectors and adopt policies designed specifically to remove these constraints. The evidence in this book overwhelmingly dispels the false notion of Africa's inability to compete globally in manufacturing goods.